Media Puzzle Edukasi untuk Meningkatkan Aktivitas dan Hasil Belajar Siswa - Rona Norhana Dewi (Jurnal Didaktika Pendidikan Dasar, 2020)
The research objective is to improve the learning activity and competency through “Puzzle Edukasi” of the seventh-grade students in SMPN 6 Tanjung in the Academic Year 2018/2019. The learning material consisted of Norm and Justice. The year 2018/2019. The design used classroom action research implemented in two cycles. Every cycle has four phases, they are planning, implementing, action, observation, and reflection. The research subjects recruited 12 male and 12 female students. Observation, tests, and questionnaires are used as instruments for data collection. Based on the finding and discussion, it can be concluded that students’ activity and competency of VII A of SMPN 6 Tanjung were improved through “Puzzle Edukasi” media. It is shown by the average score of the students’ activity, which was improved from the first cycle to the second cycle. On other hand, students’ response toward learning is dominant. Students agreed that learning PPKn with Puzzle Edukasi media can improve learning activity and competency as well as much as 96.88%.